Optimierung von Organisationsstrukturen für die emotionale und soziale Entwicklung? - Laubenstein, Désirée; Scheer, D. (In: Sonderpädagogische Förderung heute, 66. Jahrgang, Nr. 2,)

Lattice reductions and their applications to cryptographic systems - Siemer, Jan Niklas

Selbstkonzept und Klassenlehrkraftverhalten - Befunde vergleichender Analysen zu Schülerinnen und Schülern mit sonderpädagogischem Förderbedarf in der emotionalen und sozialen Entwicklung. - Zdoupas, Philippos; Laubenstein, Désirée

Digitale Räume geben und nehmen: Unterrichtsinteraktion in DSH-Kursen während der COVID-19-Pandemie. - Stenzel, Nadja; Müller, Mareike; Drumm, Sandra (Informationen Deutsch als Fremdsprache 48)

Performance Analysis of FHE Libraries - Anonymous, Anonymous

Automated SEM Image Analysis of the Sphere Diameter, Sphere-Sphere Separation, and Opening Size Distributions of Nanosphere Lithography Masks - Riedl, Thomas; Lindner, Jörg (Microscopy and Microanalysis)
Abstract Colloidal nanosphere monolayers—used as a lithography mask for site-controlled material deposition or removal—offer the possibility of cost-effective patterning of large surface areas. In the present study, an automated analysis of scanning electron microscopy (SEM) images is described, which enables the recognition of the individual nanospheres in densely packed monolayers in order to perform a statistical quantification of the sphere size, mask opening size, and sphere-sphere separation distributions. Search algorithms based on Fourier transformation, cross-correlation, multiple-angle intensity profiling, and sphere edge point detection techniques allow for a sphere detection efficiency of at least 99.8%, even in the case of considerable sphere size variations. While the sphere positions and diameters are determined by fitting circles to the spheres edge points, the openings between sphere triples are detected by intensity thresholding. For the analyzed polystyrene sphere monolayers with sphere sizes between 220 and 600 nm and a diameter spread of around 3% coefficients of variation of 6.8–8.1% for the opening size are found. By correlating the mentioned size distributions, it is shown that, in this case, the dominant contribution to the opening size variation stems from nanometer-scale positional variations of the spheres.
Keywords: Instrumentation

Optical Arbitrary Waveform Measurement (OAWM) on the Silicon Photonic Platform - Fang, Dengyang; Zazzi, Andrea; Müller, Juliana; Daniel, Drayß; Füllner, Christoph; Marin-Palomo, Pablo; Mashayekh, Ali Tabatabaei; Das, Arka Dipta; Weizel, Maxim; Gudyriev, Sergiy; Freude, Wolfgang; Randel, Sebastian; et al. (OSA Technical Digest)

Roll-Off Factor Analysis of Optical Nyquist Pulses Generated by an On-Chip Mach-Zehnder Modulator - De, Souvaraj; Singh, Karanveer; Kress, Christian; Das, Ranjan; Schwabe, Tobias; Preußler, Stefan; Kleine-Ostmann, Thomas; Scheytt, J. Christoph; Schneider, Thomas (IEEE Photonics Technology Letters)

Wie erleben Lehramtsstudierende unterschiedliche Feedbacksituationen im Praxissemester? – Analysen auf Basis einer Interviewstudie zum Einsatz von Unterrichtsvideografien - Rogge, Tim; Vogelsang, Christoph; Pollmeier, Pascal (Seminar)

Die Konstruktion der medizinischen Deutungsmacht auf Inter* - Krämer, Anike (Trans* und Inter* Studies - Aktuelle Forschungsbeiträge aus dem deutschsprachigen Raum)

Making Biological Binarity - Geschlechtszuweisende (Genital-)Operationen bei intergeschlechtlichen Kinden - Krämer, Anike; Sabisch, Katja (Geschlecht: divers. Die "Dritte Option" im Personenstandsgesetz - Perspektiven für die Soziale Arbeit)

Die (Un)Gewissheit der Zweigeschlechtlichkeit. Aushandlungen von Eltern intergeschlechtlicher Kinder - Krämer, Anike (Gewissheit. Beiträge und Debatten zum 3. Sektionskongress der Wissenssoziologie)

Geschlecht als Zäsur. Zum Alltagserleben von Eltern intergeschlechtlicher Kinder - Krämer, Anike

Anderssein akzeptieren - Krämer, Anike (Frankfurter Rundschau)

Kompetenzentwicklung im inklusiven Unterricht (KinU) – eine internationale Perspektive - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank (Grenzen. Gänge. Zwischen. Welten. Kontroversen – Entwicklungen – Perspektiven der Inklusionsforschung)

Kooperation von Lehrkräften im inklusiven Unterricht - Hoya, Fabian Karl; Hellmich, Frank (Empirische Pädagogik)

Conventional and Machine Learning Approaches for Network and Service Coordination - Schneider, Stefan Balthasar
Network and service coordination is important to provide modern services consisting of multiple interconnected components, e.g., in 5G, network function virtualization (NFV), or cloud and edge computing. In this paper, I outline my dissertation research, which proposes six approaches to automate such network and service coordination. All approaches dynamically react to the current demand and optimize coordination for high service quality and low costs. The approaches range from centralized to distributed methods and from conventional heuristic algorithms and mixed-integer linear programs to machine learning approaches using supervised and reinforcement learning. I briefly discuss their main ideas and advantages over other state-of-the-art approaches and compare strengths and weaknesses.
Keywords: nfv; coordination; machine learning; reinforcement learning; phd; digest

Zur Wirkung der universitären DaZ-Weiterbildungen an den Standorten Duisburg-Essen, Münster und Paderborn. Auswertung von schriftlichen Reflexionen teilnehmender Lehrkräfte - Asmacher, Judith; Borowoski, Damaris; Böttger, Lydia; Islinger, Günter; Robers, Christin (Universitäre Weiterbildungen im Handlungsfeld von Deutsch als Zweitsprache)

Einflüsse einer Sprachlernerfahrung auf die Professionalisierung angehender DaF/DaZ-Lehrkräfte. Ergebnisse einer Analyse von Portfolioeinträgen und Ableitung eines Modells - Groh, Olga; Böttger, Lydia; Niederhaus, Constanze (Universitäre Weiterbildungen im Handlungsfeld von Deutsch als Zweitsprache)

Silicon Photonic Radar Transmitter IC for mm-Wave Large Aperture MIMO Radar Using Optical Clock Distribution - Kruse, Stephan; Gudyriev, Sergiy; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Scheytt, Christoph (IEEE Microwave and Wireless Components Letters)

Optically clocked switched-emitter-follower THA in a photonic SiGe BiCMOS technology - Weizel, Maxim; Scheytt, J. Christoph; Kärtner, Franz X.; Witzens, Jeremy (Optics Express)

Integration fachwissenschaftlicher und fachdidaktischer Komponenten in der Lehramtsausbildung Mathematik Grundschule am Beispiel einer Veranstaltung zur Leitidee „Daten, Häufigkeit und Wahrscheinlichkeit“ - Frischemeier, Daniel; Podworny, Susanne; Biehler, Rolf (Konzepte und Studien Lehrinnovationen in der Hochschulmathematik . Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematikzur Hochschuldidaktik und Lehrerbildung Mathematik)

Ashe, Bertram D.; Saal, Ilka (eds.). Slavery and the Post-Black Imagination. Seattle: Washington University Press, 2020. 248 pp. - Hartmann, Alexandra (Kritikon Litterarum)
Keywords: Materials Chemistry; Economics and Econometrics; Media Technology; Forestry

The Sounds of Hope: Black Humanism, Deep Democracy, and Black Lives Matter - Hartmann, Alexandra (Race, Religion, and Black Lives Matter)

Perceptions of Inclusion of Students with Behavioral, Emotional and Social Difficulties (BESD) - online. - Zdoupas, Philippos; Laubenstein, Désirée

„Power-Posen“ – Fakten, frisierte Daten, Forschungslyrik? Eine Unterrichtsreihe zu Praktiken und Darstellungsformen psychologischer Forschung - Scharlau, Ingrid; Patrzek, Justine; Schreiber, Christine (Unterrichtsmaterial des Verbandes der Psychologielehrerinnen und –lehrer)
Keywords: Unterrichtsfach Psychologie

MaComp 3. Auflage, Kommentar: Rundschreiben 05/2018 (WA) - Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten - Krimphove, Dieter

Rechtsethologie - Die Arbleitung des Rechts aus der Entwicklungsgeschichte des Menschen - Krimphove, Dieter

Das Wertpapierinstitutsgesetz - oder die Etablierung eines neuen Aufsichtssystems für Finanzdienstleister - Krimphove, Dieter (Compliance Berater)

Künstliche Intelligenz im Recht - eine Übersicht - Krimphove, Dieter (JURA)

Arbeitsrechtliche Rechtssprechung des EuGH im Jahre 2020 - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Reverse Factoring im internationalen Wirtschaftsverkehr - Krimphove, Dieter (Corporate Finance)

Tesco Stores - oder das Recht europäischer Arbeitnehmer, sich unmittelbar auf die Gleichwertigkeit ihrer Arbeit zu berufen - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Der Kopftuchstreit zum wiederholten Mal oder: Das neue einheitliche "Bekenntnisreichen-Recht" - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Banken: "Mitarbeiter-Zuverlässigkeit" - Krimphove, Dieter; Lüke, Christoph (Compliance Berater)

Die neue MaRisk (BA) - Krimphove, Dieter (Zeitschriften für Bank- und Kapitalmarktrecht BKR)

"Akademisierung" des Handwerks - Krimphove, Dieter (GewArch)

Die Europäisierung der MaComp - Krimphove, Dieter (Compliance Berater)

Arbeitsrechtliche Rechtsprechung des EuGH im Jahre 2021 - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Das neue Geldwäschestrafrecht aus ökonomischer Sicht - Krimphove, Dieter (GWuR)

Ebenen der genetischen Analyse komplexer Phänotypen am Beispiel der Anorexia nervosa und der Varianz des Körpergewichts - Hirtz, Raphael; Zheng, Yiran; Rajcsanyi, Luisa S.; Libuda, Lars; Antel, Jochen; Peters, Triinu; Hebebrand, Johannes; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)
Zusammenfassung. Genetische Varianten beeinflussen die Gewichtsregulation und die Entwicklung von Essstörungen. Zunächst haben familienbasierte, sogenannte formalgenetische Studien den erblichen Anteil an der Gewichtsregulation und an der Ätiologie von Essstörungen beleuchtet. In einer Vielzahl von Studien zeigten sich sowohl für die Varianz des Körpergewichts als auch für die Entstehung von Essstörungen Erblichkeitsschätzer (Heritabilitätsraten) von über 50 %. Mit diesem Wissen begab man sich in den 90er-Jahren des letzten Jahrhunderts auf die Suche nach den zugrundeliegenden Genen (genauer: genetischen Varianten), die das Körpergewicht, das Essverhalten oder beide Phänotypen auf Grundlage geteilter Mechanismen beeinflussen. Zunächst wurden Kandidatengenstudien durchgeführt. Dabei untersuchte man auf Grundlage unterschiedlicher, v. a. aber pathophysiologisch plausibler Überlegungen Gene mit hoher Relevanz für die untersuchten Phänotypen. Dieser Ansatz war für Essstörungen nicht sehr erfolgreich, für die Gewichtsregulation konnte eine Handvoll Gene identifiziert werden. Verbunden mit großen methodischen Fortschritten in der genetischen Forschung und v. a. der Etablierung sogenannter genomweiter Assoziationsstudien (GWAS) Anfang der 2000er-Jahre konnten bislang über 1000 Varianten/Genorte detektiert werden, die das Körpergewicht beeinflussen. Für die Essstörung Anorexia nervosa (AN) sind aktuell acht solcher Genorte beschrieben. Diese Ergebnisse, aber auch aktuelle Ansätze zu phänotypübergreifenden Analysen lassen Einblicke in die komplexe Regulation des Körpergewichtes zu und haben zudem unerwartete Pathomechanismen für AN aufgezeigt.
Keywords: Psychiatry and Mental health; Clinical Psychology; General Medicine; Pediatrics; Perinatology and Child Health

La memoria du chancelier Rolin - Kamp, Hermann (Quand flamboyait la toison d’or. Le Bon, le Téméraire et le Chancelier Rolin (1376-1462). Exposition à Beaune (4 décembre 2021 – 31 mars 2022))

Exzessive Gewalt gegen Fremde. Ihre Darstellung und Bewertung in der Geschichtsschreibung um 1300 - Kamp, Hermann (Konzepte und Funktionen der Gewalt im Mittelalter)

Zwischen den Stühlen? – Verknüpfung von Erfahrungen des Praxissemesters mit Theorien im Lehramtsstudium Chemie. Sukzessiven Kompetenzaufbau nach dem Praxissemester gestalten - Pollmeier, Pascal; Fechner, Sabine (Theorie und Praxis in der Lehrerbildung - Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

Förderung angehender Lehrkräfte im Umgang mit Evidenzen für den naturwissenschaftlichen Unterricht - Pollmeier, Pascal; Fechner, Sabine (Lehrkräftebildung neu gedacht. Ein Praxishandbuch für die Lehre in den Naturwissenschaften und deren Didaktiken)

Artificial Intelligence and the Sociotechnical Imaginary: On Skynet, Self-Healing Swarms and Slaughterbots - Weber, Jutta (Drone Imaginaries. The Power of Remote Vision)

From Optimizing Military Operations to Targeting Terrorist Networks: Social Network Analysis in Data-Driven Warfare - Weber, Jutta; Mayer, Katja (Explorations in Digital Cultures)

Human-Machine Learning und Digital Commons - Weber, Jutta (In digitaler Gesellschaft. Neukonfigurationen zwischen Robotern, Algorithmen und Usern)

Auto-Mobilitätsmanagement? Über eine gelebte Vision Zero, repetitive Fortschrittsversprechen und gerechte Mobilität - Weber, Jutta (Autonome Autos. Medien- und kulturwissenschaftliche Perspektiven auf die Zukunft der Mobilität)

Expanding Technosecurity Culture. On Wild Cards, Imagination and Disaster Prevention - Weber, Jutta (Sensing In/Security: Sensors and the Making of Transnational Security Infrastructures)

How to tell machines what to do. Wissenschaftler(innen)biografien in einem Padlet darstellen - Hohwiller, Peter; Bauer, Maike (Der fremdsprachliche Unterricht Englisch)

John Lanchester’s The Wall in the advanced language classroom - Hohwiller, Peter (Teaching Transhumanism)

Zentrale Themen der Ideengeschichte physikdidaktischer Forschung in Deutschland anhand ausgewählter Originalquellen

Development of a Dynamic Strategy to Determine the Optimal Barrel Temperature of Single Screw Extruders - Köllermeier, Jonas; Schöppner, Volker (36th International Conference of the Polymer Processing Society (PPS))

Du Châtelet, Émilie (1706–1749) - Hagengruber, Ruth (Encyclopedia of Early Modern Philosophy and the Sciences)
Of the many outstanding female philosophers of the European Enlightenment, Emilie Du Châtelet excelled as a physicist, a philosopher, and a mathematician, as well as a Bible critic. She was famous in her lifetime and was not completely forgotten thereafter. Among her admirers, correspondents and friends were the most acknowledged scholars of her time, including Voltaire, Clairault, Maupertuis, Diderot, Helvetius, La Mettrie, Buffon, Christian Wolff, Leonard Euler, and Johann II Bernoulli. Her philosophical work enjoyed high reputation and her opus magnum, the Institutions physiques, was translated into Italian and German and proved her to be an intellectual of European stature. Its defense of living forces and its implied forecast into dynamics as well as her methodological grounding of scientific knowledge as hypothetical, impacted philosophy and science. Reality must by nature escape us. What we perceive are phenomena. Du Châtelet explains the function of space and time to trace us back to the origin of phenomena. Her influence on Kant is evident. Next to her writings in physics, mathematics, philosophy, language, and logic, she contributed to morality and ethics. Du Châtelet left an opus of quite systematic breadth. This impressive publishing activity excels in the amount of its scientific and philosophical production to which a vast collection of manuscripts must be added.She argued against prejudice and idolatry in philosophy and science. Science is a cooperative undertaking over history and beyond nations. Her moral writings align with ideas of the French materialists. Du Châtelet translated and commented on Newton’s Principia, preparing thus the fertile soil of the generation of physicists to come in France.
Keywords: aura Bassi Luise Gottsched Immanuel Kant Dourtous de Mairan Johann II Bernoulli Algarotti Buffon d’Alembert La Mettrie Principle of contradiction Hypotheses Enlightenment Leibniz-Clarke Correspondence Living forces Dead forces; happiness Space Imaginary beings Monads Epicurus Ethics Women philosophers Newton’s laws Principia Motion inertia Active force Vis viva Vis mortua Hypothetic reasoning Hypotheses; a priori principles; Experience; Dead forces; Living forces; Energy Dynamics

Women in Early Modern Philosophy and Science: An Introduction - Hagengruber, Ruth Edith (Encyclopedia of Early Modern Philosophy and the Sciences)
Essential ideas significantly connected to humanism, Renaissance, and early modern philosophy stem from women’s pens. The supportive role of women in the early modern period has hardly been recognized up to today. The relevant issues women have contributed to range from commentaries on and critiques of the Bible, and their demands for equality and the critique of political institutions, topics that became eminent enhancers of political and societal change in the relevant period of early modern philosophy, to enlightenment philosophy.

Bourdieu and the Quest for Intercultural Transformations - Pöllmann, Andreas (SAGE Open)
Building and expanding on Bourdieu’s notions of cultural capital, habitus, and field, this conceptual article aims to contribute to a better understanding of intercultural transformations. Distancing itself from essentialist reductionism in the analysis of cultures, it associates intercultural transformations with habitus crises through “culture shock,” with the realization of intercultural capital, and with changes in the scope and configuration of cultural pluriformity. In going beyond Bourdieu without abandoning him along the way, the approach outlined in the course of this article combines a range of conceptual tools which may prove to be useful in sustaining struggles for social justice in educational institutions and in society at large.
Keywords: General Social Sciences; General Arts and Humanities

When do firms highlight their effective tax rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren (Accounting and Business Research)
Keywords: Accounting; Finance

Zur maschinellen Entscheidungsfindung im Recht - Krimphove, Dieter; Niehaus, Sebastian

Funnel control of the Fokker-Blanck equation for a multidimensional Ornstein-Uhlenbeck process - Berger, Thomas (SIAM Journal on control and Optimization)

Linear relations and their singular chains - Berger, Thomas; de Snoo, H.; Trunk, C.; Winkler, H. (Methods of Functional Analysis and Topology)

Fault tolerant funnel control for uncertain linear systems - Berger, Thomas (IEEE Transactions on Automatic Control)

Output tracking for a non-minimum phase robotic manipulator - Berger, Thomas; Lanza, Lukas Johannes (IFAC-PapersOnLine)

Tracking control for underactuated non-minimum phase multibody systems - Berger, Thomas; Drücker, S.; Lanza, Lukas Johannes; Reis, T.; Seifried, R. (Nonlinear Dynamics)

Funnel control for the monodomain equations with the FitzHugh-Nagumo model - Berger, Thomas; Breiten, T.; Puche, M.; Reis, T. (Journal of Differential Equations)

Funnel control of nonlinear systems - Berger, Thomas; Ilchmann, A.; Ryan, E. P. (Mathematics of Control, Signals, and Systems)

Quantum detector tomography of a high dynamic-range superconducting nanowire single-photon detector - Schapeler, Timon; Höpker, Jan Philipp; Bartley, Tim (Superconductor Science and Technology)

Cryogenic Second-Harmonic Generation in Periodically Poled Lithium Niobate Waveguides - Bartnick, Moritz; Santandrea, Matteo; Höpker, Jan Philipp; Thiele, Frederik; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Herrmann, Harald; Silberhorn, Christine; Bartley, Tim (Physical Review Applied)

„Kein Grund zum Feiern“. Die Jubiläen der Universität Hamburg 1969 und 1994 im Zeichen politischer Konflikte - Becker, Rieke
Keywords: Universitätsgeschichte; Universität Hamburg; Universitätsjubiläen; Hochschuljubiläen; Jubiläumskultur; Festkulturforschung

Gottfried Wilhelm Leibniz: zu Besuch bei Ferdinand von Fürstenberg - Lauert, Markus (Leben am Hof zu Neuhaus. Biografische Skizzen zur Hofkultur einer fürstbischöflichen Residenz)

Students in the spotlight: Using collaborative autoethnography to build a community of learning in the Corona crisis - Steinhardt, Isabel (ISA Pedagogy Series)
Due to the Corona crisis, German Higher Education Institutions had to close their campuses in March and lecturers had to teach online. To understand how the Corona crisis affected students, first this article explains the structural and social inequalities in the German higher education system, using Tinto's (1975; 1997) student engagement theory. Second, the concept of Bergman-Rosamond et al. (2020) is used to analyze the challenges that Corona has raised for students, including current surveys. We found that the closure of the social space campus (and the Corona crisis as a whole) particularly hit hard those students who had previously been affected by (intersectional) inequality. Therefore, to lessen the specific challenges associated with the ad hoc transition to digital studying, the creation of a digital community of learning can help. We demonstrate how such a community can be created by the example seminar, "Digital practices: an autoethnographic observation". During the seminar, students recorded their digital technology use in a journal, and we analyzed the diary entries using the collaborate autoethnography method. The seminar example shows that this method is well suited for the development of a community of learning as it not only places students in the spotlight but as students work together on a topic they get to know each other, and a basis of trust is created through peer-feedback. Therefore, it was important to have a digital space (in this case Mahara) where the exchange could take place. The continuous insight into the students’ "learning status" enabled the lecturer to promote the learning and provide individual assistance for the students.
Keywords: Intersectionality; inequality; gender; diversity; higher-education; crisis

Opening up and Sharing Data from Qualitative Research: A Primer - Steinhardt, Isabel; Fischer, Caroline; Heimstädt, Maximilian; Hirsbrunner, Simon David; Ikiz-Akinci, Dilek; Kressin, Lisa; Kretzer, Susanne; Möllenkamp, Andreas; Portzelt, Maike; Rahal, Rima-Maria; Schimmler, Sonja; Wilke, René; et al.
The call for free access to research data and materials is becoming louder and louder from the political and scientific communities in Germany. More and more researchers are facing demands to open up qualitative research data for scientific purposes. They often have a general interest in sharing their data, but are unsure how to proceed. This handout was developed to provide an initial introduction to opening and sharing qualitative data. It was developed at a workshop held in Berlin in January 2020, organized by the research group „Digitization of Science“ of the Weizenbaum Institute, together with its associate researcher Dr. Isabel Steinhardt from the University of Kassel. The workshop involved staff from German research data centers as well as mentees and mentors from the Fellow Program Open Science who already have experience with Open Science, qualitative research, and interdisciplinary research. The handout is addressed primarily to qualitatively researching scientists in Germany. For this reason, it was initially written in German. One year later, we have now decided to translate the handout into English as well. The reasons are twofold: first, we want to make it accessible to researchers in Germany with little knowledge of German. Second, we also want to give interested people outside Germany an insight into the German system and the German discussion about opening up and sharing qualitative data. Due to the objectives and the history of its development, the handout focuses on the German context. This includes the literature references and further sources, and the references to research data centers as well as legal issues. We have deliberately not included a contextualization of the German situation in international discussions in order to keep the handout as short as possible.

Digitale Praktiken und das Studium - Steinhardt, Isabel (Entwicklungen im Feld der Hochschule)
Anhand einer explorativen Studie in den Fächern Jura und Soziale Arbeit wird rekonstruiert welche Praktiken Studierende in Bezug auf digitale Technologien haben und ob digitale Praktiken im Studium existieren. Dazu wurden narrative Interviews mit sechs Studierenden geführt, die habitushermeneutisch ausgewertet wurden. Die Ergebnisse zeigen keine digitalen Praktiken in Bezug auf das Studium, wohingegen sich digitale Praktiken im alltäglichen Leben zeigen. Für das Studium zeigen sich unterschiedliche Praktiken in der Nutzung digitaler Technologien, die in Beziehung zu den Kapitalsorten stehen, die Studierende besitzen. Die explorativen Ergebnisse legen nahe, dass Studierende unterschiedliche Hilfestellungen in Bezug auf die Digitalisierung des Studiums benötigen, die in der Lehrplanung und -pädagogik berücksichtigt werden müssten.

Hochschulinnenpolitik. Mikropolitische Verhältnisse der Hochschuldidaktik - Steinhardt, Isabel (Handbuch Hochschuldidaktik)
Die Hochschuldidaktik wurde in den letzten zehn Jahren flächendeckend an deutschen Hochschulen ausgebaut, da die Qualität der Lehre als Faktor im nationalen wie auch internationalen Wettbewerb der Hochschulen angesehen wird. In diesem Beitrag wird untersucht, wie sich dieser Ausbau mikropolitisch in der Arena Hochschule niederschlägt. Hierzu wurden eine systematische Literaturauswahl durchgeführt und mittels qualitativer Inhaltsanalyse einschlägige Texte der Hochschuldidaktiker:innen analysiert. Für die theoriegeleitete qualitative Inhaltsanalyse wurden als deduktive Kategorien die von Crozier und Friedberg (1993) benannten Machtquellen Expertise, Kommunikations- und Informationsflüsse, organisationale Regeln und Umweltkontakte verwendet. Fazit der Untersuchung ist, dass die Hochschuldidaktik zwar viele Stellen hinzugewonnen hat, es allerdings kaum einen Zuwachs an Macht gab, der nun in die Entscheidungs- und Aushandlungsprozesse innerhalb der Hochschulen eingebracht werden könnte.
Keywords: Mikropolitik; Macht; Machtquellen; Positionseffekte; Hochschuldidaktik

Permanent provisionality: The homes of mobile managerial professionals between temporariness and permanence - Spiegel, Anna (Transitions: Journal of Transient Migration)
Nowadays, mobility and transience are no longer exclusively associated with the marginalized and socially excluded, such as homeless or displaced people. On the contrary, mobility and transience have become a constitutive pattern of the highly skilled postmodern workforce. Yet, how mobile professionals negotiate the meaning of their homes in âliquid timesâ and what homemaking practices they use to deal with the temporal uncertainty of their homes are questions that still require further research. This article â based on ethnographic research on German and American managers conducted in China, Germany and the United States between 2011 and 2014 â contributes to this research question by examining how mobile professionals make sense of the transience of their current homes and how transience is reflected in their homemaking practices. The article argues that for mobile professionals the home becomes a critical place not only because of new multilocal spatialities but also because of new transient temporalities. Due to the corporate practice of giving successive temporary contracts, the mobile managersâ everyday life is characterized by a âpermanent provisionalityâ, that is, an incongruence of the initially imagined and the actual time horizons of their mobility. This article shows how this âpermanent provisionalityâ is worked into the material and social textures of expatriate homes.

3D-Druck - Eine Technologie als Schlüssel zur Steigerung der Teilhabe - Kruse, Anne; Ott, Manuel; Risse, Lena; Koch, Rainer

Experimental failure analysis of adhesively bonded steel/CFRP joints under quasi-static and cyclic tensile-shear and peel loading - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (International Journal of Adhesion and Adhesives)
Keywords: Epoxy adhesive; fatigue strength; shear; peel; Steel-CFRP joints

Homotopic approach for turnpike and singularly perturbed optimal control problems - Cots, Olivier; Gergaud, Joseph; Wembe Moafo, Boris Edgar (ESAIM: Proceedings and Surveys)
The first aim of this article is to present the link between the turnpike property and the singular perturbations theory: the first one being a particular case of the second one. Then, thanks to this link, we set up a new framework based on continuation methods for the resolution of singularly perturbed optimal control problems. We consider first the turnpike case, then, we generalize the approach to general control problems with singular perturbations (that is with fast but also slow variables). We illustrate each step with an example.
Keywords: Immunology

Brand names as multimodal constructions. On the role of typography as an additional indicator of onymisation. - Dübbert, Alexander (Linguistics Vanguard)
Brand names are a common part of the everyday consumer environment, and can be found on countless visual surfaces such as food packaging. A key characteristic of brand names is their fixed design. Many brand names owe their linguistic form to units that originally did not constitute proper names. They developed into brand names through complex sub-processes of what is commonly referred to as onymisation. These processes include semantic, morphological and phonological/graphemic changes. The aim of this paper is to explore how the specific typographic design of a brand name can be an additional indicator in its process of onymisation. After clarifying the concepts of onymisation and typographic design, an extended multimodal construction model is presented. The basis of the paper is an analysis of a corpus of image data comprising more than 600 photographs of food packaging. In order to get a first impression of how the multimodal constructions of brand names could look, an omission test following a suggestion by Ziem (2017) is applied to the data.

Geometric and Numerical Methods in Optimal Control and Zermelo Problems on Revolution Surfaces - Applications - Wembe Moafo, Boris Edgar

Sozialpädagogische Qualifizierungen weiterdenken - Göddertz, Nina (Sozial Extra)
Viele Wege führen in die sozialpädagogische Praxis, doch nach wie vor stellt sich die Frage, wie sozialpädagogisches Handeln gelernt und gelehrt werden kann. Unter Bezugnahme auf kritisch bildungstheoretisch-fundierte Ansätze plädiert der Beitrag für eine Weiterentwicklung einer kritischen Didaktik der beruflichen Fachrichtung Sozialpädagogik.
Keywords: Fachdidaktik Sozialpädagogik Kritische Bildungstheorie Emanzipation und Mündigkeit

Concept development of a method for identifying friction coefficients for the numerical simulation of clinching processes - Böhnke, Max; Rossel, Moritz Sebastian; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The International Journal of Advanced Manufacturing Technology)
Abstract In order to reduce fuel consumption and thus pollutant emissions, the automotive industry is increasingly developing lightweight construction concepts that are accompanied by an increasing usage of aluminum materials. Due to poor weldability of aluminum in combination with other materials, mechanical joining methods such as clinching were developed and established in series production. In order to predict the relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard, the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals as well as between the sheet metal and clinching tools has a significant impact on the geometrical formation of the clinched joint. No testing methods exist that can sufficiently investigate the frictional behavior in sheet materials, especially under high interface pressures, different relative velocities, and long friction paths, while allowing a decoupled consideration of the test parameters. This paper describes the development of further testing concepts based on a proven tribo-torsion test method for determining friction coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum and steel sheet material in clinching processes is investigated using numerical simulation. Based on these findings, the developed concepts focus on determining friction coefficients at interface pressures of the above materials, yield stress, as well as the reproduction of the occurring friction conditions between sheet metal materials and tool surfaces in clinching processes using tool substitutes. Furthermore, wear investigations between sheet metal material and tool surface were carried out in the friction tests with subsequent EDX analyses of the frictioned tool surfaces. The developed method also allows an optical deformation measurement of the sheet metal material specimen by means of digital image correlation (DIC). Based on a methodological approach, the test setups and the test systems used are explained, and the functionality of the concepts is proven by experimental tests using different sheet metal materials.

Concept development of a method for identifying friction coefficients for the numerical simulation of clinching processes - Böhnke, Max; Rossel, Moritz; Bielak, Christian R.; Bobbert, Mathias; Meschut, Gerson (The International Journal of Advanced Manufacturing Technology)
Abstract In order to reduce fuel consumption and thus pollutant emissions, the automotive industry is increasingly developing lightweight construction concepts that are accompanied by an increasing usage of aluminum materials. Due to poor weldability of aluminum in combination with other materials, mechanical joining methods such as clinching were developed and established in series production. In order to predict the relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard, the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals as well as between the sheet metal and clinching tools has a significant impact on the geometrical formation of the clinched joint. No testing methods exist that can sufficiently investigate the frictional behavior in sheet materials, especially under high interface pressures, different relative velocities, and long friction paths, while allowing a decoupled consideration of the test parameters. This paper describes the development of further testing concepts based on a proven tribo-torsion test method for determining friction coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum and steel sheet material in clinching processes is investigated using numerical simulation. Based on these findings, the developed concepts focus on determining friction coefficients at interface pressures of the above materials, yield stress, as well as the reproduction of the occurring friction conditions between sheet metal materials and tool surfaces in clinching processes using tool substitutes. Furthermore, wear investigations between sheet metal material and tool surface were carried out in the friction tests with subsequent EDX analyses of the frictioned tool surfaces. The developed method also allows an optical deformation measurement of the sheet metal material specimen by means of digital image correlation (DIC). Based on a methodological approach, the test setups and the test systems used are explained, and the functionality of the concepts is proven by experimental tests using different sheet metal materials.

Deutschsprachige Oratorien des 'langen 19. Jahrhunderts' : Studien zu vergessenen Gattungsbeiträgen
Der vorliegende Band versammelt die Ergebnisse eines wissenschaftlich-künstlerischen Lehrprojekts. Im Rahmen von zwei Seminaren, die an der Folkwang Universität der Künste in Essen sowie der Westfälischen Wilhelms-Universität Münster stattgefunden haben, haben sich Studierende im Sommersemester 2019 vergessenen deutschsprachigen Oratorien des »langen 19. Jahrhunderts« zugewandt und zu jeweils einem Werk einen eigenen Forschungsbeitrag verfasst. Ergänzt werden die acht Werkstudien um einen einführenden Beitrag aus theologisch-bibelwissenschaftlicher Perspektive.

MiDeCon: Unsupervised and Accurate Fingerprint and Minutia Quality Assessment based on Minutia Detection Confidence - Terhörst, Philipp; Boller, André; Damer, Naser; Kirchbuchner, Florian; Kuijper, Arjan (International IEEE Joint Conference on Biometrics, IJCB 2021, Shenzhen, China, August 4-7, 2021)

Privacy-Enhancing Face Biometrics: A Comprehensive Survey - Meden, Blaz; Rot, Peter; Terhörst, Philipp; Damer, Naser; Kuijper, Arjan; Scheirer, Walter J.; Ross, Arun; Peer, Peter; Struc, Vitomir (IEEE Trans. Inf. Forensics Secur.)

MAAD-Face: A Massively Annotated Attribute Dataset for Face Images - Terhörst, Philipp; Fährmann, Daniel; Kolf, Jan Niklas; Damer, Naser; Kirchbuchner, Florian; Kuijper, Arjan (IEEE Trans. Inf. Forensics Secur.)

Mitigating Soft-Biometric Driven Bias and Privacy Concerns in Face Recognition Systems - Terhörst, Philipp

On Soft-Biometric Information Stored in Biometric Face Embeddings - Terhörst, Philipp; Fährmann, Daniel; Damer, Naser; Kirchbuchner, Florian; Kuijper, Arjan (IEEE Trans. Biom. Behav. Identity Sci.)

PROJECT FOR THE DEVELOPMENT OF OPERATIONAL AND DEMAND-ORIENTED FIREFIGHTING EQUIPMENT - Hanses, Hendrik; Horwath, Ilona (Book of Abstracts 37th Danubia Adria Symposium on Advances in Experimental Mechanics)

Longitudinal mechanical joining of extruded aluminium profiles with increased tightness requirements - Neumann, Stefan; Meschut, Gerson; Kneuper, Florian; Hering, Oliver; Tekkaya, Erman

Herrscherhuldigung und Friedenslob – Das Opusculum cantionum des Johannes Flamingus (1571) - Höink, Dominik (Religiöse Friedensmusik von der Antike bis zur Gegenwart)

Frieden – Musik – Religion: Zur Einführung - Höink, Dominik (Religiöse Friedensmusik von der Antike bis zur Gegenwart)

Religiöse Friedensmusik von der Antike bis zur Gegenwart
Musik war seit jeher ein zentrales Medium der künstlerischen Auseinandersetzung mit dem Thema „Frieden“. Ob als gesungene Friedensbitte innerhalb von religiösen Zeremonien, als Mittel zur Formulierung von Friedenssehnsucht oder als Teil von Feierlichkeiten nach einem Friedensschluss – unzählige Beispiele aus den verschiedensten kulturellen Kontexten und Zeiten wären anzuführen. Die Beiträge im vorliegenden Band, die auf eine Tagung im Juni 2018 in Münster zurückgehen, thematisieren daher sowohl innerkompositorische Friedensbezüge als auch kontextbedingte Zuschreibungen, die sich etwa aus der Funktionalisierung für entsprechende Friedensfeiern ergeben. Durch den historischen Längsschnitt und den Einschluss von Beiträgen zur außereuropäischen und nicht-christlichen Musik ergibt sich ein weites Panorama unterschiedlichster Studien.

Kompetenzdiagnose in der Berufsbildung von Pflegelehrpersonen - Schürmann, Mirko; Bender, Elena; Grebe, Christian (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))
Zusammenfassung In diesem Beitrag der Zeitschrift Gruppe. Interaktion. Organisation. (GIO) wird das Instrument zur Diagnose pädagogischer Kompetenzen von Pflegelehrpersonen (PädKomPflege) vorgestellt. Die Berufsbildung in der Pflege ist durch sich verändernde inhaltliche und gesetzliche Anforderungen geprägt. Verschiedene landesspezifische rechtliche Vorgaben führen zu einem sehr heterogenen Bild von Qualifikationen und Kompetenzen der Pflegelehrpersonen. Die Anrechnung bereits erworbener Kompetenzen auf pflegepädagogische Studiengänge sowie die Kompetenzerfassung und -bilanzierung in Berufsbildungseinrichtungen spielt daher eine wichtige Rolle. Vor diesem Hintergrund wurde das Instrument PädKomPflege entwickelt und erprobt. Grundlage des Kompetenzmodells sind die Empfehlungen der Kultusministerkonferenz (2004) zu den Standards für die (allgemeine) Lehrerbildung sowie Expertenworkshops und -interviews mit PflegedidaktikerInnen. Die empirische Erprobung erfolgte an einer Stichprobe von 1096 Pflegelehrpersonen. Psychometrische Analysen auf Grundlage der klassischen Testtheorie sowie IRT-basierte Analysen führten zu einer Überarbeitung des Instruments, welches nun als zweisprachiges Online-Self-Assessmenttool (eng./deut.) vorliegt. Die Validierung der deutschsprachigen Version fand anhand von 545 TeilnehmerInnen im Jahr 2016 statt, sodass ein geprüftes Instrument mit 54 Items in den fünf Hauptskalen (Unterricht, Beurteilung, Beratung, Lernortkooperation sowie Organisations- und Schulentwicklung) und 18 Subskalen zur Verfügung steht. Sowohl klassische als auch probabilistische Testgütekriterien werden erfüllt. Die Skalen weisen hohe interne Konsistenzen auf ( α > 0,80) und sind überwiegend konstruktvalide. So lassen sich für 17 der 18 Subskalen ordinale Raschmodelle anpassen. Auf der Ebene der Hauptskalen können Partial Credit Modelle für alle Items von modellkonformen Subskalen einer Hauptskala angepasst werden. Das Instrument kann zur individuellen Kompetenzdiagnostik, zur Identifikation von Bildungsbedarfen in Schulen des Gesundheitswesens und im Kontext beruflicher Bildungsprozesse genutzt werden. In der Onlineversion erhalten Teilnehmende abschließend ein individuelles Kompetenzprofil mit möglichen Vergleichswerten. Das Tool kann begleitend zu Qualifizierungsprozessen als Monitoring-Instrument oder zur individuellen Kompetenzbilanzierung eingesetzt werden.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology; Developmental and Educational Psychology; Education; Social Psychology

Collaborating with Virtual Assistants in Organizations: Analyzing Social Loafing Tendencies and Responsibility Attribution - Stieglitz, Stefan; Mirbabaie, Milad; Möllmann, Nicholas R. J.; Rzyski, Jannik (Information Systems Frontiers)
Abstract Organizations increasingly introduce collaborative technologies in form of virtual assistants (VAs) to save valuable resources, especially when employees are assisted with work-related tasks. However, the effect of VAs on virtual teams and collaboration remains uncertain, particularly whether employees show social loafing (SL) tendencies, i.e., applying less effort for collective tasks compared to working alone. While extant research indicates that VAs collaboratively working in teams exert greater results, less is known about SL in virtual collaboration and how responsibility attribution alters. An online experiment with N = 102 was conducted in which participants were assisted by a VA in solving a task. The results indicate SL tendencies in virtual collaboration with VAs and that participants tend to cede responsibility to the VA. This study makes a first foray and extends the information systems (IS) literature by analyzing SL and responsibility attribution thus updates our knowledge on virtual collaboration with VAs.
Keywords: Computer Networks and Communications; Information Systems; Theoretical Computer Science; Software

The rise of artificial intelligence – understanding the AI identity threat at the workplace - Mirbabaie, Milad; Brünker, Felix; Möllmann Frick, Nicholas R. J.; Stieglitz, Stefan (Electronic Markets)
Abstract Artificial intelligence (AI) is being increasingly integrated into enterprises to foster collaboration within humanmachine teams and assist employees with work-related tasks. However, introducing AI may negatively impact employees’ identifications with their jobs as AI is expected to fundamentally change workplaces and professions, feeding into individuals’ fears of being replaced. To broaden the understanding of the AI identity threat, the findings of this study reveal three central predictors for AI identity threat in the workplace: changes to work, loss of status position, and AI identity predicting AI identity threat in the workplace. This study enriches information systems literature by extending our understanding of collaboration with AI in the workplace to drive future research in this field. Researchers and practitioners understand the implications of employees’ identity when collaborating with AI and comprehend which factors are relevant when introducing AI in the workplace.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Is it alright to use artificial intelligence in digital health? A systematic literature review on ethical considerations - Möllmann, Nicholas RJ; Mirbabaie, Milad; Stieglitz, Stefan (Health Informatics Journal)
The application of artificial intelligence (AI) not only yields in advantages for healthcare but raises several ethical questions. Extant research on ethical considerations of AI in digital health is quite sparse and a holistic overview is lacking. A systematic literature review searching across 853 peer-reviewed journals and conferences yielded in 50 relevant articles categorized in five major ethical principles: beneficence, non-maleficence, autonomy, justice, and explicability. The ethical landscape of AI in digital health is portrayed including a snapshot guiding future development. The status quo highlights potential areas with little empirical but required research. Less explored areas with remaining ethical questions are validated and guide scholars’ efforts by outlining an overview of addressed ethical principles and intensity of studies including correlations. Practitioners understand novel questions AI raises eventually leading to properly regulated implementations and further comprehend that society is on its way from supporting technologies to autonomous decision-making systems.
Keywords: Health Informatics

Recommendations for Managing AI-Driven Change Processes: When Expectations Meet Reality - Stieglitz, Stefan; Möllmann (Frick), Nicholas R. J.; Mirbabaie, Milad; Hofeditz, Lennart; Ross, Björn (International Journal of Management Practice)
Artificial intelligence (AI) has moved beyond the planning phase in many organisations and it is often accompanied by uncertainties and fears of job loss among employees. It is crucial to manage employees{’} attitudes towards the deployment of an AI-based technology effectively and counteract possible resistance behaviour. We present lessons learned from an industry case where we conducted interviews with affected employees. We evaluated our results with managers across industries and found that that the deployment of AI-based technologies does not differ from other IT, but that the change is perceived differently due to misguided expectations.
Keywords: Artificial Intelligence; Change Management; Resistance; AI-Driven Change; AI Deployment; AI Perception

Die Health Professionals Competence Scales (HePCoS) zur Kompetenzerfassung in den Gesundheitsfachberufen. Technical Report - Grebe, Christian; Schürmann, Mirko; Latteck, Änne-Dörte